Developing dairy enterprise for ensuring food and livelihood security of the poorest of poor - Srivastava, A K (Indian Farming, 2015)
Dairying in India offers immense opportunities to uplift the rural economy and to sustain the food and livelihood security of the rural masses. It is considered to be the backbone of the smallholder economy especially in case of landless producers. Nurturing the smallholder dairying in the underprivileged and rural areas through effective mechanisms including pro-poor livestock policy and location specific strategies would not only boost the country’s milk production but also substantially improve the nutritional security and poverty alleviation in rural masses. Development of region specific crossbred animal and establishment of developed germplasm repository, inventorization of local feed resources and enrichment technologies for improving the nutrient availability, regularizing milk markets and regional disease forecasting are some of the R & D areas for boosting the dairying. Agro-ecological zone specific prioritization of animals and planning considering the strengths of the particular region would unravel the hidden potential in dairying. Public private partnership (PPP) and involvement of insurance agencies for regular vaccination and monitoring of health of animals could also be a way forward for assured input delivery, health care promotion and regulated market of milk in smallholder production system.